2021
DOI: 10.1186/s13059-021-02509-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sequence motifs in the yeast 3′ untranslated region determined from massively parallel assays of random sequences

Abstract: Background The 3′ untranslated region (UTR) plays critical roles in determining the level of gene expression through effects on activities such as mRNA stability and translation. Functional elements within this region have largely been identified through analyses of native genes, which contain multiple co-evolved sequence features. Results To explore the effects of 3′ UTR sequence elements outside of native sequence contexts, we analyze hundreds of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 76 publications
0
10
0
1
Order By: Relevance
“…Yeast 3'UTRs have been proven to be able to influence gene expression, especially for regions that are UA enriched 34,35 . In this study, we found that there is a transcriptional interference region ranging from 20 to 60 bp upstream of CSs in bidirectional termination zones (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yeast 3'UTRs have been proven to be able to influence gene expression, especially for regions that are UA enriched 34,35 . In this study, we found that there is a transcriptional interference region ranging from 20 to 60 bp upstream of CSs in bidirectional termination zones (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this transcriptional interference region coincides with the region where UAUAUA motif is highly enriched. Considering UAUAUA motifs have been shown to influence gene expression in yeast 35 , we speculated that they should play a role in the formation of the transcriptional interference region. Indeed, when AS CSs fall into the transcriptional interference region of sense CSs, and when only one of them harbors UAUAUA motif, there is a great discrepancy between expression levels of sense and AS pAs (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in the 3′ UTR and terminator regions, both the presence and number of poly-A/T, positioning (consensus 5′-AAWAAA-3′) 54,65 and efficiency motifs (5′-TATDTA-3′) 27 were correlated (Spearman's ⍴ between 0.06 and 0.51, p-value < 1e−16, respectively) with the predicted expression levels (Supplementary Fig. 12), with a 9%, 6%, and 45% higher amount of motif-carrying sequences, respectively, found in the high expression sequences compared to low expression ones 26 (Fig. 5g).…”
Section: Generated Regulatory Dna Carries Sequence Determinants Of Ge...mentioning
confidence: 92%
“…Popular strategies to design synthetic regulatory DNA of varying expression levels include stacking multiple known functional sequence motifs 4,6,18,19 and applying random mutagenesis to a specific region, most commonly the promoter 8,[20][21][22][23] though also UTRs [24][25][26] and terminators 27,28 have been targeted, typically in a form of short sequence segments of <100 bp. Using in silico screening approaches 7,8 , which evaluate the fitness of candidate sequences by predicting their expression levels, more intricate solutions based on evolutionary computation 29 have been implemented, including genetic algorithms 15,24,[29][30][31] .…”
mentioning
confidence: 99%